Climate Analogue and Future Appearance of Novel Climate in Southeast Asia - Nguyen-Thi, Tuyet (Archīum Ateneo, 2020)
This study identified the analogue locations of five big cities and the future appearance of novel climate in Southeast Asia (SEA) at the end of the 21st century under the Representative Concentration Pathways 8.5 (RCP8.5) and 4.5 (RCP4.5) scenarios. A modified version of an existing formulation to estimate climate distance is introduced, using the monthly means of temperature and precipitation from six regional climate experiments and from six global climate models (GCMs). Results showed that regional downscaling allowed a more accurate representation of temperature but displayed a higher variability in rainfall over SEA compared to the GCM performance. The ensemble mean (ENS) experiment had a relatively better performance compared to each individual experiment in representing the monthly time series of temperature and precipitation. The common tendency of climatic relocation towards warmer regions for the five big cities in SEA (Hanoi, Bangkok, Manila, Kuala Lumpur and Jakarta) was prominent with the regional ENS experiment. At the end of the 21st century, the ratio of novel climate areas over SEA, mainly located in low elevation, coastal, equatorial regions, and islands, was less than 2% under RCP4.5, but increased to 24 and 21% under RCP8.5 for the ensemble regional and global experiments, respectively.